في علاجهاTannic acid ودور حامض التانكMus musculusدراسة تاثير تركيزين من كلوريد الالمنيوم على بعض المعايير الدمويه واوزان ذكور الفئران المختبرية - حسين, صباح (University of Thi-Qar Journal of Science, 2010)
The study was designed to investigate the effect of aluminum chloride of body weight and blood parameter (RBC, HB, PCV, MCV, MCH, WBC count, N., L., M., E., B.) and the role tannic acid in the treatment. The male mice which treated were randomally divided into three main groups. Each groups incloud 20 mice first control  group injected with (I.P) physiological Nacl and the other group injection in 1mg/kg,2 mg/kg respectively from saline aluminum chloride for 10 days and measurement the body weight after that killing 10 male in all groups and the anther male mice injection of 5mg/kg,10gm/kg respectively tannic acid for 5 days while control group continue injection Nacl and measurement the body weight After that killing all male mice to measurement blood parameter .